Hydrogen Generation by Water Reduction with [Cp*2Ti(OTf)]: Identifying Elemental Mechanistic Steps by Combined In Situ FTIR and In Situ EPR Spectroscopy Supported by DFT Calculations. Issue 41 (17th September 2013) - Hollmann, Dirk; Grabow, Kathleen; Jiao, Haijun; Kessler, Monty; Spannenberg, Anke; Beweries, Torsten; Bentrup, Ursula; Brückner, Angelika
Abstract A detailed mechanism of hydrogen production by reduction of water with decamethyltitanocene triflate [Cp*2TiIII(OTf)] has been derived for the first time, based on a comprehensive in situ spectroscopic study including EPR and ATR‐FTIR spectroscopy supported by DFT calculations. It is demonstrated that two H2O molecules coordinate to [Cp*2TiIII(OTf)] subsequently forming [Cp2*TiIII(H2O)(OTf)] and [Cp*TiIII(H2O)2(OTf)]. Triflate stabilizes the water ligands by hydrogen bonding. Liberation of hydrogen proceeds only from the diaqua complex [Cp*TiIII(H2O)2(OTf)] and involves, most probably, abstraction and recombination of two H atoms from two molecules of [Cp*TiIII(H2O)2(OTf)] in close vicinity, which is driven by the formation of a strong covalent TiOH bond in the resulting final product [Cp*2TiIV(OTf)(OH)].